DEGRADABILIDAD Y CINÉTICA RUMINAL IN VITRO DE ENSILAJE DE ZEA MAYS FORRAJERO Y MAGUEY DE THEOBROMA CACAO L. EN DIFERENTES PROPORCIONES - Macias Palma, Kevin Ariel (2023)
The use of agro-industrial residues for animal feed have managed to obtain an ecological value helping to avoid environmental contamination, however, these by-products can be modified for their preservation during food shortages, taking advantage of both forage and residues through silages. The objective of this research work was to evaluate the in vitro rumen degradability and kinetics of forage corn silage with cocoa maguey residue in different proportions.